ChemInform Abstract: Molecular‐Oxygen‐Promoted Cu‐Catalyzed Oxidative Direct Amidation of Nonactivated Carboxylic Acids with Azoles. Issue 4 (January 2016) - Ding, Wen; Mai, Shaoyu; Song, Qiuling
Abstract: The title reaction probably proceeds via a copper peroxycarboxylate intermediate.